2017
DOI: 10.1021/acs.orglett.7b02265
|View full text |Cite
|
Sign up to set email alerts
|

Copper- or Nickel-Enabled Oxidative Cross-Coupling of Unreactive C(sp3)–H Bonds with Azole C(sp2)–H Bonds: Rapid Access to β-Azolyl Propanoic Acid Derivatives

Abstract: β-Azolyl propanoic acid derivatives are frequently found in biologically active molecules and pharmaceuticals. Here, we report the oxidative heteroarylation of unactivated C(sp)-H bonds with azole C(sp)-H bonds via copper or nickel catalysis with the aid of removable bidentate auxiliary, which provides a rapid pathway to β-azolyl propanoic acid derivatives. A variety of azoles such as oxazole, benzoxazole, thiazole, benzothiazoles, benzimidazole, purine, and even [1,2,4]triazolo[1,5-a]pyrimidine could be engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…This DG was not restricted to the formation of C–C bonds, since very recently, the group of You demonstrated that this bidentate DG was successfully used in the oxidative amination of unactivated C(sp 3 )–H bonds with azoles via a Cu mediated process ( Scheme 104C ). 608 Note that an extension of this transformation via Ni catalysis was also reported using in that case the amide derived from 8-aminoquinoline as DG.…”
Section: Bidentate Dgsmentioning
confidence: 84%
See 1 more Smart Citation
“…This DG was not restricted to the formation of C–C bonds, since very recently, the group of You demonstrated that this bidentate DG was successfully used in the oxidative amination of unactivated C(sp 3 )–H bonds with azoles via a Cu mediated process ( Scheme 104C ). 608 Note that an extension of this transformation via Ni catalysis was also reported using in that case the amide derived from 8-aminoquinoline as DG.…”
Section: Bidentate Dgsmentioning
confidence: 84%
“…Besides its efficiency, a key advantage of this bidentate DG is its removal, which could be easily realized under basic conditions. 603 608 …”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Jingsong You and coworker in 2017 extended their work in C(sp 3 )−H hetero arylation to investigate 8‐amino quinoline as a directing group over 2‐aminopyridine N ‐oxide (Scheme ) . Instead of using equivalent amount of Cu(OAc) 2 .…”
Section: Nickel‐catalyzed Dehydrogenative Bond Formationsmentioning
confidence: 99%
“…5 Most current methods for accessing 2-alkylazoles depend on the transition metal-catalyzed direct C-2-alkylation of azoles with alkylating reagents under basic conditions. 6 However, the convenient and straightforward approach using non-functionalized ethers as alkylating reagents through crossdehydrogenative coupling is still rare. 7 Very recently, Lu and Li group also demonstrated the cobalt-catalyzed crossdehydrogenative coupling reaction of oxazoles and ethers.…”
mentioning
confidence: 99%
“…We also found that the yield of 3a was decreased using the reported CoCO 3 catalyst under relatively mild conditions ( Table 1, entry 3). Furthermore, basic mesoporous Cu/METS-10, Fe/METS-10 and Ni/METS-10 were also prepared to investigate in our catalytic cycle, and the results demonstrated that Co/METS-10 exhibited the higher catalytic efficiency, indicating that Co/METS-10 is the optimal catalyst (Table 1, entries [4][5][6]. Aer that, replacement of TBHP with other additives, such as K 2 S 2 O 8 , 2,3-dichloro-5,6dicyanobenzoquinone (DDQ), di-tert-butyl peroxide (DTBP), dicumyl peroxide (DCP), benzoyl peroxide (BPO) and t-BuOOBz, caused either the low yield of desired product 3a or no reaction, suggesting that THBP is the optimal additives (Table 1, entries 7-12).…”
mentioning
confidence: 99%